(untitled) (The Pakistan Development Review, 2009)
Dr Ishfaq Ahmad, Deputy Chairman, Planning Commission, Dr Rashid Amjad, President, Pakistan Society of Development Economists, Dr G. M. Arif, Secretary Pakistan Society of Development Economists, Excellencies, Ladies and Gentlemen! It is indeed a privilege and honour to address this distinguished gathering of economists and social scientists. Over the years the Annual Conference of the Pakistan Society of Development Economists has become one of the leading events on the calendar of meetings where experts from various disciplines discuss cutting edge issues that confront developing economies in general and Pakistan’s economy in particular. I want to especially congratulate the Society and the President on completing 25 years as it celebrates its Silver Jubilee. I am very happy that the founding President, Prof. Dr Nawab Haider Naqvi is with us today and that some of the past Presidents are also present. The Pakistan Institute of Development Economics, the home of the Society, also needs to be congratulated for holding such conferences on an annual and regular basis. I am very happy that this meeting as in the past is being attended by internationally acclaimed economists and academics from both within and outside the country. I am especially heartened to see that students of economics from all over Pakistan have been especially invited to attend this meeting.